Simulated changes in vegetation distribution, land carbon storage, and atmospheric CO2 in response to a collapse of the North Atlantic thermohaline circulation - Köhler, Peter; Joos, F.; Gerber, S.; Knutti, R. (Climate Dynamics, 2005)
Measurements on glacial ice show that atmospheric CO2 varied by 20ppmv with large iceberg discharges into the North Atlantic (NA) and themost prominent Dansgaard/ Oeschger (D/O) climate fluctuations. CO2variations during less pronounced D/O events were smaller than a fewppm. The D/O fluctuations have been linked to changes in the NAThermohaline Circulation (THC). Here, we analyse how abrupt changes inthe NA THC affect the terrestrial carbon cycle by forcing theLund-Potsdam-Jena Dynamic Global Vegetation Model with climateperturbations from freshwater experiments with the ECBILT-CLIOgeneral circulation model. Changes in the marine carbon cycle are notaddressed. Modelled NA THC collapsed and recovered after about amillennium in response to prescribed freshwater forcing. The initialcooling of several Kelvin over Eurasia causes a reduction ofextant boreal and temperate forests and a decrease in carbon storage inhigh northern latitudes, whereas improved growing conditions andslower soil decomposition rates lead to enhanced storage inmid-latitudes. The magnitude and evolution of global terrestrialcarbon storage in response to abrupt THC changes depends sensitivelyon the initial climate conditions. Terrestrial storage varies between-67 and +50 PgC for arange of experiments that start at different times during the last21,000 years. Simulated peak-to-peak differences in atmospheric CO2and d13C are between {6 and 18 ppmv} and $0.18$ and $0.30$~\mypermil and compatible with the ice core CO2 record.